Clinical epidemiology of familial sarcoidosis: A systematic literature review - Terwiel, Michelle; van Moorsel, Coline H.M. (Respiratory medicine, 2019)
Although the presence of familial sarcoidosis has been confirmed, clinical and epidemiological data on its characteristics are scattered and sometimes paradoxical. The objective of this review is to assess what is known on the clinical epidemiology of familial sarcoidosis, by combining data from early case reports with recent population based data; aiming to support in clinical decision making and providing information to patients. A systematic review of the literature in PubMed was done and 27 studies with clinical or epidemiological data on familial sarcoidosis, published between 1947 and 2017, were included. The pooled prevalence proportion of familial sarcoidosis, based on twelve study populations, was 9.5% (CI 4.6–16.1), highest in French, African American, Dutch and Irish patients. A heritability of 60–70% was estimated in diverse studies. Relative types and relationships most often reported in familial sarcoidosis were siblings and mother-child relationships. Familial risk is heterogeneous. In African Americans specific environmental factors have been associated with familial sarcoidosis (OR between 1.5 and 3.2). European American and African American subjects had different relative risks for first degree familial relationships (OR of 16.6 vs 3.1) and relative risk differed between relative types. Clinical findings in familial sarcoidosis are still obscure. Prevalence of familial sarcoidosis is high in specific study populations from countries worldwide. The estimated heritability of 60–70%, suggests a shared determinant, and the heterogeneous familial risk, associated with both genetic and environmental factors. Familial relative risks and clinical phenotypes may differ between ethnic groups and relative types, but require further study. •Family members of patients with sarcoidosis are more likely to develop sarcoidosis.•Pooled prevalence of familial sarcoidosis from heterogeneous studies is 9.5%.•Estimated heritability of 60–70% in diverse studies suggests a shared determinant.•Characteristics of familial sarcoidosis differ between study populations.